Hey, what about me?: a video guide for brothers and sisters of new babies. ([s.l.] : Goldhil Entertainment.)
Find out what to expect with a new baby in the family. Watch kids like you getting to know about being big brothers and big sisters. Enjoy original songs about your feelings, and learn games, lullabies, and bouncing rhymes to play with the baby. You'll discover how some things change, but a lot stays the same.